USING GOOGLE MEET IN TEACHING SPEAKING - Afief fakhruddin (Universitas Majalengka, 2018)
The aim of this research was to investigate how the use of google meet could improve students’ speaking skills of English deparments’ students in semester four of Universitas Majalengka. This particular research was categorized as action research. The actions were implemented in two cycles based on the class schedule. This research involved the twenty two students. The data of the study were in the forms of qualitative and quantitative data. The qualitative data were obtained by observing the teaching and learning process of speaking. Meanwhile, the quantitave data were acquired through test. The research findings showed that the use of google meet as the teaching media combined with the use of speaking activities and classroom English was proven to be effective to improve the students’ speaking skills.